MAKING HERBAL SULFUR SOAP AS AN ALTERNATIVE TO CHILDREN'S SKIN HEALTH CARE AT MAMIYAI ORPHANAGE - Girsang, Emilia; Saragih, Mandra; Yolanda, Fani Miftah; Anggraini, Wahyu Ella; Gaol, Rotua Lumban (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2025)
This study aims to develop and analyze the effectiveness of herbal sulfur soap as an alternative skin health care for children at Mamiyai Orphanage. The background of the study was based on the high prevalence of skin problems such as dermatitis, eczema, and fungal infections experienced by children in orphanages due to limited hygiene facilities and lack of skin care knowledge. Sulfur soap was chosen due to its antimicrobial and anti-inflammatory properties that have been proven to be effective in treating various skin problems, and is easily produced locally at low cost. Research methods included observation, interviews, and analysis of the effectiveness of sulfur soap on children's skin conditions. The results showed that regular use of sulfur soap can reduce symptoms of skin diseases and improve overall skin health. This study recommends the use of sulfur soap as an affordable and practical solution to improve the quality of life and self-confidence of children in orphanages.This study aims to develop and analyze the effectiveness of herbal sulfur soap as an alternative skin health care for children at Mamiyai Orphanage. The background of the study was based on the high prevalence of skin problems such as dermatitis, eczema, and fungal infections experienced by children in orphanages due to limited hygiene facilities and lack of skin care knowledge. Sulfur soap was chosen due to its antimicrobial and anti-inflammatory properties that have been proven to be effective in treating various skin problems, and is easily produced locally at low cost. Research methods included observation, interviews, and analysis of the effectiveness of sulfur soap on children's skin conditions. The results showed that regular use of sulfur soap can reduce symptoms of skin diseases and improve overall skin health. This study recommends the use of sulfur soap as an affordable and practical solution to improve the quality of life and self-confidence of children in orphanages.